Bawaslu's Authority to Resolve Disputes on Elected Candidates Internal to Political Parties in the 2024 Legislative Election - Salahudin Pakaya; Ismet Hadi; Irwansyah Reza Mohamad; Suslianto Suslianto; Sitti Magfirah Makmur; Moh. Amin Dali (Journal La Sociale, 2024)
The open proportional system used in the 2024 Legislative Election with the determination of elected legislative candidates within political parties based on the majority of votes has resulted in disputes over elected candidates within political parties. This research aims to determine the provisions governing procedures for resolving disputes between internal political party candidates and institutions authorized to resolve disputes. The research method used is normative with descriptive analysis looking at Bawaslu's authority in resolving cases based on reports from fellow legislative candidate members within the party. The authority to determine elected candidates as legislative members is in the hands of the KPU/KPUD in stages. Thus, political parties cannot intervene in this authority in any form. The research results found that Bawaslu as the institution responsible for supervising the stages or process of elections as attributed to the Election Law, should be able to handle or resolve disputes between internal legislative candidates of political parties because it is explicitly stated in the academic text of Law no. 7 of 2017 that Bawaslu received and reviewed reports regarding alleged violations of Election Administration Provisions because disputes over elected candidates within political parties were included in the election dispute regime and not the political party dispute regime. The conclusion of this research is that this type of dispute can occur in the election process, especially in the process of determining elected legislative candidates by the KPU, provincial KPU, district/city KPU.